2010
DOI: 10.1016/j.otsr.2010.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage reconstruction of post-traumatic segmental tibia bone loss with nailing

Abstract: Level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(91 citation statements)
references
References 8 publications
2
86
0
3
Order By: Relevance
“…Hence, most of the reported cases are segmental bone defect of the diaphyseal part of the long bones [5,11,[13][14][15][16][17][18][19][20][21][22]. In our experience, we used this technique mostly for the tibia and the femur but also for the humerus and the radius.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Hence, most of the reported cases are segmental bone defect of the diaphyseal part of the long bones [5,11,[13][14][15][16][17][18][19][20][21][22]. In our experience, we used this technique mostly for the tibia and the femur but also for the humerus and the radius.…”
Section: Remaining Questionsmentioning
confidence: 99%
“…Similar to our own findings, previous studies on the induced membrane technique (usually with ICBG) reported bone union rates of 89% to 100% (see Table, Supplemental Digital Content 3 http://links.lww.com/BOT/A679, treatment of bone defect with the induced membrane technique). 5,7,11,14,[25][26][27] The size of the bone defect, the bone segment involved, and the bone defect type were not related to the time to achieve bone union. This is one of the advantages of the technique, because bone union is not directly related to the defect size.…”
Section: Discussionmentioning
confidence: 94%
“…This because of poor control of known factors: surgeon failure, implant failure, patient and physiotherapy related failures [1][2][3]. This rate is not far from the 10% to 16% found by Moyikoua et al working almost in similar conditions [6]. Unbearable pain 1 2 3 4 2-How much does your injury Currently interfere with your normal/usual necessary activity (including prolonged standing, walk-in, stairs, car driving and sleeping)?…”
Section: Discussionmentioning
confidence: 99%
“…The protocol for the treatment is two-stage management; first removal of the fixator and eradication of infection if any. The second stage includes stabilization of fracture and bone grafting to stimulate bone healing and halting non-union [6][7][8]. The of the current work aims at assessing the final functional outcomes of the proposed two-stage management of non-union after failed ring external fixation.…”
Section: Introductionmentioning
confidence: 99%